Keadaan Koleksi Terawat Untuk Meningkatkan Sirkulasi Di Perpustakaan Universitas Indonesia - Aprilia, Putri; Ginting, Richard Togaranta; Kastawa, Made (Jurnal Ilmiah Ilmu Perpustakaan dan Informasi, 2016)
ABSTRACT                The title of this research is "Maintained Collection to Increase Circulation in the Indonesia University’s Library". This type of research is quantitative methods. The population of this reseacrhs is taken directly from permanent library users as much as 62.900 during the last 3 months, counted from January to March 2016 and results in a sample of 400 people through a calculation using the Slovin formula.This research taken for two weeks from 27 April 2016 to 11 May 2016, on 2nd floor at Indonesia University’s Library.               The results can be obtained through this research there are still widely found users who try to damage the collection either intentionally or accidentally as many as 29.3% or 117 people, but the condition of collections in the University Library Indonesia had pretty good in 40.3% or as many as 161 users.Keyword : Preservation, Maintained Collection, Library of Indonesian University.